Role of the parasympathetic nervous system in cardioprotection by remote hindlimb ischemic preconditioning - Donato, Pablo Martín (2013)
This investigation was designed to determine the participation of the vagus nerve and muscarinic receptors in the remote ischaemic preconditioning (rIPC) mechanism. New Zealand rabbits were anaesthetized, and the femoral artery was dissected. After 30 min of monitoring, the hearts were isolated and subjected to 30 min of global no-flow ischaemia and 180 min of reperfusion (non-rIPC group). The ventricular function was evaluated, considering the left ventricular developed pressure and the left ventricular end-diastolic pressure. In the rIPC group, the rabbits were subjected to three cycles of hindlimb ischaemia (5 min) and reperfusion (5 min), and the same protocol as that used in non-rIPC group was then repeated. In order to evaluate the afferent neural pathway during the rIPC protocol we used two groups, one in which the femoral and sciatic nerves were sectioned and the other in which the spinal cord was sectioned (T9-T10 level). To study the efferent neural pathway during the rIPC protocol, the vagus nerve was sectioned and, in another group, atropine was administered. The effect of vagal stimulation was also evaluated. An infarct size of 40.8 ± 3.1% was obtained in the non-rIPC group, whereas in rIPC group the infarct size decreased to 16.4 ± 3.5% (P < 0.05). During the preconditioning protocol, the vagus nerve section and the atropine administration each abolished the effect of rIPC on infarct size. Vagal stimulation mimicked the effect of rIPC, decreasing infarct size to 15.2 ± 4.7% (P < 0.05). Decreases in infarct size were accompanied by improved left ventricular function. We demonstrated the presence of a neural afferent pathway, because the spinal cord section completely abolished the effect of rIPC on infarct size. In conclusion, rIPC activates a neural afferent pathway, the cardioprotective signal reaches the heart through the vagus nerve (efferent pathway), and acetylcholine activates the ischaemic preconditioning phenomenon when acting on the muscarinic receptors.